Pedicle Subtraction Osteotomy for the Correction of Post-tubercular Kyphotic Deformity in the Thoraco-lumbar Region: A Clinical Outcome Study - Islam, K M Rafiqul; Chowdhury, Sharmin; Majid, Ahsan; Rahman, Md Moshiur; Forhad, Sheikh; Siddiqui, Erfanul Huq; Alam, Md Shamsul; Khan, Mohammed Ramzanul Karim; Rahaman, Md Motiur; Hossain, Md Sazzad (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Post-tubercular kyphosis results from vertebral collapse, instability, and canal compromise, leading to progressive pain and neurological risk. Pedicle subtraction osteotomy (PSO) enables single-stage correction through wedge resection of the posterior column and pedicles with an anterior cortical hinge. Materials and Methods: This prospective study was conducted in the Department of Orthopaedic Surgery, BSMMU, Dhaka, from March 2021 to September 2023. Fifteen patients with symptomatic thoraco-lumbar post-tubercular kyphosis underwent single-level PSO. Outcomes were assessed pre-operatively and at 1, 3, 6, and 12 months using the visual analogue scale (VAS), Oswestry disability index (ODI), kyphotic angle, Bridwell fusion criteria, Denis’s work scale, and modified Macnab’s criteria. Statistical analysis was performed using SPSS v29.0. Results: The study included 10 males and 5 females (mean age 38.6 ± 14.27 years). Farmers (33.3%) and day labourers (26.7%) were most affected. All patients had back pain, weakness, and kyphosis; 53.3% had gait abnormality, 26.7% sensory disturbance, and 6.7% bowel/bladder involvement. L1 was the most common PSO level (66.7%). Complications included one intraoperative dural tear (6.7%), one wound infection (6.7%), and one implant failure (6.7%). Mean hospital stay was 16.7 ± 2.94 days. Mean VAS improved from 7.2 ± 0.41 to 2.4 ± 0.59 (p < 0.001). ODI improved from 55.27 ± 5.06 to 14.0 ± 6.70 (p < 0.001). Mean kyphotic angle improved from 42.51° ± 3.10 to 5.34° ± 0.85 (correction 37.39° ± 0.83, p < 0.001). Radiological fusion (Bridwell grade I) was achieved in 93.3% at 12 months. At one year, 80% had excellent and 20% good outcomes. Conclusion: PSO is a safe and effective procedure for correcting post-tubercular kyphotic deformity, providing significant pain relief, functional improvement, solid fusion, and restoration of sagittal alignment. J Bangladesh Coll Phys Surg 2025; 43: 265-268